The problem with courtesy - Ramšak, Jure (Poligrafi, 2025)
particularly in comparison with the neighbouring republic of Croatia, where the ethnicization of religion, beginning in the early 1970s, was rather pronoun-ced, relations between the Catholic Church and state authorities in Slovenia – the northernmost republic of Yugoslavia – remained relatively calm and cooperative throughout the late socialist period. Based on an analysis of a wide range of pu-blic and archival documents, this paper demonstrates how Slovenian religious policy was proposed as a sophisticated example of how believers could be success-fully integrated into modern socialist society, and was presented as such to Vati-can diplomats, international experts, and foreign journalists. Up until 1990, the communication between party officials and the Church hierarchy conveyed a di-stinct tone of courtesy, and local priests generally encountered a supportive or at least unobstructive attitude when, for instance, proposing the construction of new churches. At the same time, however, the more independent intellectuals, Catholi-cs and Marxists alike, who urged the party to abandon its orthodox Marxist-Leni-nist understanding of religion in favour of a genuine dialogue, were marginalized. Thus, a proper debate about a topic so essential for socialist secular society never took place, and the late socialist religious policy left behind an ambiguous legacy.
Keywords: Church-State relations; civil rights of believers; civilne pravice vernikov; Jugoslavija; odnosi med Cerkvijo in državo; samoupravni socializem; self-management socialism; Slovenia; Slovenija; Yugoslavia